Relationship between ABO blood groups and preeclampsia - Nanhathai Mahasub; Dittakarn Boriboonhirunsarn (Taylor & Francis Group, 2020)
Objective To investigate the relationship between ABO blood group and preeclampsia.Methods: A case-control study was conducted, including 230 and 460 women with and without preeclampsia. ABO blood groups were compared and associated factors for preeclampsia were determined.Results: Blood group O was significantly more common in early-onset and less common in late-onset preeclampsia. Regression analysis showed that blood group O decreased the risk of late-onset preeclampsia (aOR 0.63, 95%CI 0.42-0.93) but increased the risk of early-onset preeclampsia (aOR 1.97 95%CI 1.05-3.69).Conclusion: Blood group O decreased the risk of late-onset preeclampsia while it increased the risk of early-onset preeclampsia.